32: A Randomized Controlled Trial Comparing Ultrasound, Veinviewer and Standard Approach to Peripheral Intravenous Catheter Placement in the Pediatric Emergency Department. Issue 6 (1st June 2014) - Curtis, SJ; Craig, W; Erin, L; Vandermeer, B; Hanson, A; Klassen, T
Abstract: BACKGROUND: Peripheral IV (PIV) line placement is painful, stressful and is the most common procedure performed in the pediatric emergency department (PED). First attempt cannulation success rates are variable and practitioner dependent. OBJECTIVES: The primary objective of this study was to investigate whether the use of either ultrasound or VeinViewer could improve the rate of success of the initial attempt at PIV placement in comparison to the current standard approach. Secondary objectives were to investigate, when compared to standard approach, whether the use of ultrasound or VeinViewer 1) reduced the number of IV punctures required to achieve successful PIV placement, 2) reduced the time taken to achieve successful PIV placement, 3) improved nursing satisfaction with PIV placement in children. DESIGN/METHODS: Prospective, randomized controlled trial, stratified by age, comparing three PIV placement approaches: 1) ultrasound 2) VeinViewer 3) standard traditional approach. All children aged 0 to 16, requiring PIV for routine care in the PED, were approached for enrollment. RESULTS: Four hundred patients were enrolled. Overall success of IV placement on first attempt was similar across study arms: Standard (109 of 146 [74.7%]); Ultrasound (97 of 137 [70.8%]); VeinViewer (89 of 135 [65.9%]); P=0.28. When stratified, differences were also non-significant. For age three and under: Standard (31 of 50 [62.0%]); Ultrasound (22 of 42 (52.4%)); Vein Viewer: (18 of 43 [41.9%]); P=0.15. For age four and above: Standard (78 of 96 [81.3%]); Ultrasound (75 of 95 [79.0%]); Vein Viewer (71 of 92 [77.2%]), P=0.77. Overall mean number of attempts did not differ significantly between groups: Standard (1.43); Ultrasound (1.40); VeinViewer (1.58). Overall time variables across groups were not significantly different. Mean times from verbalization of study arm to successful PIV were: Standard (14.8 min); Ultrasound (17.6 min), VeinViewer (16.1 min); P=0.44. Mean times from tourniquet to time of successful PIV were: Standard (6.5 min); Ultrasound (8.3 min); VeinViewer (7.8 min); P=0.50. Nurse satisfaction was not improved by use of either technology. CONCLUSIONS: We found no evidence that either Ultrasound or VeinViewer improves the first-attempt success rate, number of cannulation attempts, speed of cannulation for children or nursing satisfaction in the pediatric emergency department.